2009
DOI: 10.1080/10643380701798264
|View full text |Cite
|
Sign up to set email alerts
|

In-vehicle Exposure to Carbon Monoxide Emissions from Vehicular Exhaust: A Critical Review

Abstract: Vehicle-induced emissions constitute a major source of air pollutants, particularly in urban areas, where heavy traffic is common occurrence. Contaminated air can flow into enclosed micro-environments, including vehicle compartments. Among various exhaust emissions, carbon monoxide (CO) was the first indicator examined in passenger compartments. This paper presents a critical review of worldwide research work conducted to characterize CO exposure inside vehicles. Measurement methodologies for field testing are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…As indicated in Fig 2, COVID-19-induced decreases in human activity, especially in transportation, most significantly affected the levels of both pollutants. The findings indicated that CO and NO2 in Thailand are mainly generated from incomplete combustion and the internal combustion of vehicles (Carslaw et al, 2019;El-Fadel and Abi-Esber, 2009). In case of the secondary pollutant, O3 exhibited different pattern between…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As indicated in Fig 2, COVID-19-induced decreases in human activity, especially in transportation, most significantly affected the levels of both pollutants. The findings indicated that CO and NO2 in Thailand are mainly generated from incomplete combustion and the internal combustion of vehicles (Carslaw et al, 2019;El-Fadel and Abi-Esber, 2009). In case of the secondary pollutant, O3 exhibited different pattern between…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Past reviews of travelers' pollution exposure have been oriented by pollutant (Kaur et al, 2007;Knibbs, Cole-Hunter, & Morawska, 2011) and/or focused on in-vehicle exposures (El-Fadel & Abi-Esber, 2009). These reviews focused on exposure concentrations and provide little or no discussion of respiration or its effects on intake and uptake doses.…”
Section: Introductionmentioning
confidence: 99%
“…For windows open mode in cars, the dilution rate was the highest due to natural ventilation provided by the wind. The variation of the dilution rate is explained by the air exchange rates compiled by [28] for stationary vehicles.…”
Section: Dilution Rate Of In-vehicle Co For Various Ventilation Settingsmentioning
confidence: 99%